2011
DOI: 10.1128/aac.05265-11
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Artemether-Lumefantrine and Nevirapine-Based Antiretroviral Therapy in HIV-1-Infected Patients

Abstract: Artemether-lumefantrine and nevirapine-based antiretroviral therapy (ART) are the most commonly recommended first-line treatments for malaria and HIV, respectively, in Africa. Artemether, lumefantrine, and nevirapine are metabolized by the cytochrome P450 3A4 enzyme system, which nevirapine induces, creating potential for important drug interactions. In a parallel-design pharmacokinetic study, concentration-time profiles were obtained in two groups of HIV-infected patients: ART-naïve patients and those stable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
55
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(77 citation statements)
references
References 36 publications
19
55
3
Order By: Relevance
“…Our findings are consistent with those of Kredo et al (6) and confirm that drug-drug interactions between AL and NVP are potentially important. However, NVP stimulation of the CYP3A4 isoenzyme would be expected, a priori, to lower peripheral lumefantrine levels, due to an increase in the amount of lumefantrine metabolized to desbutyl-lumefantrine, a potent derivative that is normally found at a concentration between 0.5% and 5% of that of the parent compound at day 7 in the few studies available (8,20).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Our findings are consistent with those of Kredo et al (6) and confirm that drug-drug interactions between AL and NVP are potentially important. However, NVP stimulation of the CYP3A4 isoenzyme would be expected, a priori, to lower peripheral lumefantrine levels, due to an increase in the amount of lumefantrine metabolized to desbutyl-lumefantrine, a potent derivative that is normally found at a concentration between 0.5% and 5% of that of the parent compound at day 7 in the few studies available (8,20).…”
Section: Discussionsupporting
confidence: 83%
“…Our findings corroborate the findings of Kredo et al (6) in a larger group of AL-treated individuals, some of whom were infected with P. falciparum. Insufficient parasitological data were available to determine whether this difference in lumefantrine concentration provides any parasitological benefit to NVP-treated HIV patients with malaria infections.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The reported effects of nevirapine-based ART on lumefantrine exposure are variable (Table 2) (8,10,11,13,14,22). Our study reports ϳ50% lower lumefantrine exposure, consistent with findings reported from a Ugandan nonlinear mixed-effects modeling study (8,22).…”
Section: Downloaded Fromsupporting
confidence: 81%
“…The overall lower lumefantrine exposure may be due in part to a decrease in oral bioavailability resulting from increased intestinal P-glycoprotein or CYP3A4 expression or to the 30-to 60-min delay in food intake in the nevirapine-based ART group (23). While reported studies were all conducted with adults, there were differences in study design (parallel groups, crossover, or historical controls), pharmacokinetic analysis (intensive sampling, population modeling, or day 7 sampling only), sample size, patient characteristics (malaria infection status, race, ethnicity, and gender), and food intake that may underlie these differences (8,10,11,13,14,22,24).A significant limitation of our study is the use of healthy historical controls as the comparator group. While the sampling protocols were nearly identical and assays were conducted in the same laboratory, differences in demographic features, ethnicity, and HIV status between subjects enrolled in the control and nevirapine-based ART groups are important (16,18,25).…”
mentioning
confidence: 84%